2019
DOI: 10.1002/alr.22415
|View full text |Cite
|
Sign up to set email alerts
|

Impact of margin status on survival after surgery for sinonasal squamous cell carcinoma

Abstract: BackgroundSinonasal squamous cell carcinoma (SNSCC) is the most common malignancy of the paranasal sinuses. Surgery is the mainstay of treatment, yet positive surgical margins (PSM) are common and the prognostic impact on overall survival (OS) is mixed. Given the heterogeneity of impact of PSM on OS within the literature, we hypothesized that extent of tumor extirpation (microscopic PSM vs macroscopic PSM) may play a role in OS.MethodsPatients with SNSCC were identified in the National Cancer Database (NCDB, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…The absence of data on locoregional recurrence within the NCDB renders any explanation for this phenomenon speculative, yet the question warrants consideration. A recent NCDB analysis demonstrated that approximately 30% of SNSCC resections result in positive surgical margins, half of which are grossly positive, attributable to anatomic proximity to the brain and orbit 17 . This has been shown to adversely affect OS 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of data on locoregional recurrence within the NCDB renders any explanation for this phenomenon speculative, yet the question warrants consideration. A recent NCDB analysis demonstrated that approximately 30% of SNSCC resections result in positive surgical margins, half of which are grossly positive, attributable to anatomic proximity to the brain and orbit 17 . This has been shown to adversely affect OS 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent NCDB analysis demonstrated that approximately 30% of SNSCC resections result in positive surgical margins, half of which are grossly positive, attributable to anatomic proximity to the brain and orbit 17 . This has been shown to adversely affect OS 17 . One possibility is that the signal of long‐term survival benefit in regional control gained by END is obscured by failure of local control with surgical margin positivity in this subsite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For sinonasal cancers, complete resection with clear margins significantly impacts oncologic outcomes in patients treated with minimally invasive endoscopic resection. 8,21 Despite the fact that intraoperative frozen margins are reliably interpreted for sinonasal tumors, 22 a clear demarcation of tumor from normal tissue or inflamed polypoid tissues is difficult within the sinonasal cavity. In the current study we demonstrate that endoscopic fluorescence imaging can be sensitive and specific to detect the tumor after systemic administration of a NIR tumor-targeting agent.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, rates of positive margins for endoscopic surgery for SNSCC are high (22-30%), which can result in increased local recurrence and decreased survival. 7,8 Fluorescence-guided surgery (FGS) is increasingly being studied as a guide to differentiate tumor tissue from normal tissue in an intraoperative setting. 9 Although several agents are under active clinical study, [10][11][12][13] we investigated the anti-epidermal growth factor receptor (EGFR) antibody-dye conjugate panitumumab-IRDye800CW, which has demonstrated a high sensitivity and specificity of squamous cell carcinoma (SCC) detection in patients with head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%